Hiv-1 Resistance Patterns to Integrase Inhibitors in Chilean Patients with Virological Failure on Raltegravir-Containing Regimens - Beltran-Buendia, C (Elsevier Ltd, 2020)
In this viewpoint we would like to describe our results in terms of resistance pattern in Chilean patients with virological failure (VF) on raltegravir (RAL)-containing-regimens and highlight the need for the concomitant availability of genotypic resistance testing to integrase strand transfer inhibitors (INSTIs) introduction in antiretroviral regimens, particularly in countries in South America. Indeed we found in our study the presence of two or more primary mutations in some of the participants which is associated with cross-resistance to all INSTIs. By using timely genotyping, we could optimally manage these patients, early after detection of VF. 2055-6640/© 2020 The Author(s).